(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we study a generalization of Mersenne numbers and we introduce an extension of Fermat numbers, we find their generating functions binet formulas, related matrix representation and many other properties. Also, we provide some applications in cryptography